Training and Work Motivation as Determinants of Employee Performance in Public Sector Organizations - Veranita, Mira; Ramayani Yusuf; Gunardi (International Journal Administration, Business & Organization, 2026)
This study aims to analyze the influence of training and work motivation on employee performance at the Bandung Regency Land Office, both partially and simultaneously. The study used a mixed-methods approach with a sequential explanatory design. Quantitative data were collected through questionnaires from 78 employees and analyzed using partial least squares-based structural equation modeling. Qualitative data were obtained through in-depth interviews with leaders, supervisors, and implementing employees to enrich the interpretation of the quantitative results. The results indicate that training and work motivation have a positive and significant effect on employee performance. Work motivation has a stronger influence than training. Simultaneously, these two variables explain a significant portion of the variation in employee performance. Qualitative findings reveal that training effectiveness is influenced by the suitability of the material to job requirements and organizational support, while work motivation is driven primarily by the meaning of work and public service orientation. This study concludes that improving employee performance in public organizations requires integrated management of training and work motivation, supported by an adequate work environment and leadership.